EDUCATION OF MORAL QUALITIES IN PRESCHOOL CHILDREN (Web of Teachers: Inderscience Research, 2025)
The task and content of the moral education of children of preschool age requires the education and development of the child's spiritual world, his mind, moral feelings, and personal qualities. Education of moral feelings, ideas and behavior in children. Providing moral knowledge fulfills a number of educational tasks, a broad vision and understanding of the moral values of human life and culture is provided.